Narrative and ethnographic perspective in a fragment of Nueva corónica of Felipe Guaman Poma - Arana Bustamante, Luis (2011)
This study focuses on the «Platica y conuerzacion de los pretenciores», a brief section of Guaman Poma de Ayala’s chronicle of c.1615. It considers a way of analysing the information and the author’s vision of the early Andean colonial system which show his procedures in social observation and narrative construction. It also makes some remarks about his special social position and doublesided cultural formation.